Efektivitas Gamifikasi dalam Meningkatkan Keterampilan Berbicara Arab Siswa Madrasah Aliyah - Shofiyani, Amrini; Mahliatussikah, Hanik; Barry, Muhammad Yasin Fatchul (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to analyze the effectiveness of gamification in learning Arabic speaking skills (maharah al-kalam) at the Madrasah Aliyah level. Using a quasi-experimental pretest-posttest control group design, the research involved 60 tenth-grade students in Jombang, East Java, divided into an experimental group (gamification-based learning using the Quizizz platform and leaderboard) and a control group (traditional lecture and structured exercise-based learning). Data were collected through speaking skill tests, motivation and language anxiety questionnaires, participatory observation, and semi-structured interviews with teachers and students. Quantitative data were analyzed using independent t-tests and effect size calculations (Cohen's), while qualitative data were analyzed using the Miles and Huberman interactive analysis model. The results show that gamification significantly improved students' Arabic speaking skills (p < 0.05; d = 1.76) by fostering a low-anxiety, interactive, and student-centered learning environment. Student participation increased from 40% to over 85%, accompanied by gains in vocabulary mastery, speaking fluency, motivation, self-confidence, and emotional engagement. Effective activities included role-play, simulations, word-guessing games, and information gap tasks. The study concludes that systematic gamification integration is an effective pedagogical approach for enhancing oral communicative competence, highlighting the importance of teacher training to ensure sustainable learning outcomes.